2013
DOI: 10.1186/1477-3155-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles of Albizia adianthifolia: the induction of apoptosis in human lung carcinoma cell line

Abstract: BackgroundSilver nanoparticles (AgNP), the most popular nano-compounds, possess unique properties. Albizia adianthifolia (AA) is a plant of the Fabaceae family that is rich in saponins. The biological properties of a novel AgNP, synthesized from an aqueous leaf extract of AA (AAAgNP), were investigated on A549 lung cells. Cell viability was determined by the MTT assay. Cellular oxidative status (lipid peroxidation and glutathione (GSH) levels), ATP concentration, caspase-3/-7, -8 and −9 activities were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 39 publications
(43 reference statements)
4
67
0
3
Order By: Relevance
“…Mitochondrial permeability has been associated with various metabolic consequences, such as halted electron transport, generation of ROS, and decreased production of ATP. 90,91 Collectively, our results suggest that AgNPs of both sizes upregulate caspase mRNA; however, 10 nm particles produced a significantly stronger effect than the 20 nm particles, and TM3 cells were more sensitive than TM4 cells.…”
mentioning
confidence: 67%
“…Mitochondrial permeability has been associated with various metabolic consequences, such as halted electron transport, generation of ROS, and decreased production of ATP. 90,91 Collectively, our results suggest that AgNPs of both sizes upregulate caspase mRNA; however, 10 nm particles produced a significantly stronger effect than the 20 nm particles, and TM3 cells were more sensitive than TM4 cells.…”
mentioning
confidence: 67%
“…Figure 2A shows the XRD pattern obtained from the culture supernatant of B. tequilensis. The presence of peaks at 2θ values of 32.0° and 45.7° corresponds to (111) and (200) planes of silver, respectively. Thus, the XRD spectrum confirmed the crystalline structure of AgNPs.…”
Section: Xrd Analysis Of B-agnps and F-agnpsmentioning
confidence: 99%
“…Previous studies have shown that AgNPs have cytotoxic effects in different cell types and apoptosis-inducing properties. 20,25,41 In vitro apoptosis/necrosis assay Further experiments were conducted with fluorescein isothiocyanate-annexin V and PI staining and flow cytometric analysis. During early apoptosis, phosphatidyl serins (PS) in the membrane translocate to the outer leaflet of the cell membrane.…”
Section: Analysis Of Apoptosis-related Gene Expressionmentioning
confidence: 99%
“…In addition, the rate of reduction of metal ions using plant extracts has been found to be much faster compared to microorganisms, and the stable formation of metallic NPs has been studied. 18 Several reports are available in the literature on the green synthesis of AgNPs using various plant extracts, including those from Plumbago zeylanica, 19 Albizia adianthifolia, 20 Pulicaria glutinosa, 21 Eucalyptus leucoxylon, 22 Acacia leucophloea, 23 Chrysanthemum indicum L., 24 Achillea biebersteinii, 25 and Lantana camara. 26 Therefore, many plant-based products have been used in the synthesis of AgNPs.…”
Section: Introductionmentioning
confidence: 99%